2010
DOI: 10.1136/thx.2009.129296
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ homeostasis and structural and functional remodelling of airway smooth muscle in asthma

Abstract: Asthma is characterised by airway hyper-responsiveness and remodelling, and there is mounting evidence that alterations in the phenotype of airway smooth muscle (ASM) play a central role in these processes. Although the concept that dysregulation of ASM Ca 2+ homeostasis may underlie at least part of these alterations has been around for many years, it is only relatively recently that the availability of ASM biopsies from subjects with mild and moderate asthma has allowed it to be properly investigated. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 62 publications
1
56
2
Order By: Relevance
“…We hypothesized that dysregulation of ASM functions via epigenetic modifications of gene expression may contribute to AHR because of the ASM's proliferative, contractile, and secretory properties (25,26). As a test of concept, we used the ASM cells isolated from trachea of control animals and HDM-challenged mice, and tested for the methylation status and expression of six potential candidate genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that dysregulation of ASM functions via epigenetic modifications of gene expression may contribute to AHR because of the ASM's proliferative, contractile, and secretory properties (25,26). As a test of concept, we used the ASM cells isolated from trachea of control animals and HDM-challenged mice, and tested for the methylation status and expression of six potential candidate genes.…”
Section: Resultsmentioning
confidence: 99%
“…The model we studied leads to AHR after an acute allergen sensitization and challenge, and we hypothesize that this occurs by activating a set of genes responsible for ASM contraction, proliferation, and remodeling. ASM is postulated to play an important role in asthma pathophysiology because of its proliferative and migration phenotypes, together with its contractile and secretory properties (25,26). Airway remodeling involves thickening of the airway wall and increase in ASM mass (27).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in agonist-induced calcium responses in BSMCs contribute to a stronger contractile response of the airways, a characteristic feature of asthma. Elevation of [Ca 21 ] i can result from increased Ca 21 influx from the extracellular fluid and Ca 21 release from the sarcoplasmic reticulum (SR) (11). In smooth muscle cells, excitation-contraction coupling involves depolarization of the plasma membrane to open voltage-gated calcium (Ca 21 ) channels.…”
mentioning
confidence: 99%
“…Agonist-induced calcium release is largely from the SR (12,14). Ca 21 efflux from the SR is mediated by the SR-Ca 21 release channel, known as ryanodine receptor (RyR), and inositol 1,4,5-trisphosphate receptors (11 In the present study, we investigated the effects of IL-5, IL-13, and TNF-a on the calcium response of BSMCs to contractile agonists and on the interaction of FKBP12.6 with RyR2 in asthmatic AHR in vivo and in vitro. We found, for the first time, that chronic airway allergic inflammation causes dissociation of FKBP12.6 from RyR2 in BSMCs and enhances Ca 21 release response from the SR, leading to AHR in asthma.…”
mentioning
confidence: 99%
“…In vitro studies showed these drugs are responsible for increasing the levels of cAMP described as a regulatory second messenger of intracellular calcium-dependent mechanisms. Calcium is one of several molecules responsible for the smooth muscle contraction during acute phase of asthma crises (Mahn et al, 2010). Of note, side effects are observed in patients under 2-agonists therapy, mainly cardiac frequency increases in response to activation of cardiac 1-receptors.…”
Section: Conventional Treatment Of Allergic Diseasesmentioning
confidence: 99%